Rapid assessment model on risk management based on ISO 31000:2018. Issue 1 (1st July 2022) - Hardjomidjojo, H; Pranata, C; Baigorria, G
Abstract: Risk management is an integral part of the management process to identify potential risks an organisation faces and mitigation measures to eliminate the impact of risks. The organisation is committed to managing risk consistently and continuously. The application of Risk Management in decision analysis can improve the organisation's operational performance and competitive value. ISO 31000:2018 is a standard guide, instructions, and requirements for an organisation to build a foundation and framework for a risk management program. This research aims to design a model for rapid assessment of risk management implementation based on ISO 31000:2018. The rapid assessment model developed is supported by a specific and detailed model to have detailed information about the factors that the company should improve. The rapid assessment model is based on three parts of risk management of ISO 31000:2018 according to "three lines of defence"; risk owners, risk control and compliance and risk assurance. The total number of factors measured in the rapid assessment model is 43; 9 factors for the first part, 15 for the second part, and 19 for the last part. A specific and detailed model consists of 481 measurements; 24 factors for the first part, 171 for the second part, and 286 for the last part. A trial of the model has been done for measuring the performance of risk management implementation in two agroindustries; herbal and instant beverage companies. The result shows that both companies are categorised as "well implemented" for operational risk management by using the rapid assessment model. Based on the results using a specific and detailed model, the herbal agroindustry is categorised as "well implemented" for risk management operation in the company, while for the instant beverage company, the risk management is already "implemented but needs improvement". Thus, the instant beverage company should increase its performance in complying with ISO 31000:2018 based on the lowest scored measurement in the result.